A New Fuzzy Decision-making Procedure to Prioritization of the Brand City Candidates for Turkey - Erdogan, Melike; Bilisik, Ozge N.; Kaya, Ihsan (OLD CITY PUBLISHING INC, 2018)
City branding is a concept that is particularly emphasized in recent years. The purpose of that case is the cities are in a competition with each other to attract more tourists and thus to contribute to the development of the regional and national economy. In this sense, to determine the brand value of the city and compare cities relatively to highlight the city with the highest brand value is very important concept. For this aim, we try to determine the priorities among candidate brand cities in Turkey and to propose a fuzzy multi-criteria decision making (MCDM) methodology consists of fuzzy Analytic Network Process (ANP) and Delphi Method. The Delphi Method has been applied to use for selection of city alternatives that must be primarily supported. The extension of ordinary fuzzy ANP method is hold to get results closer to the truth with incorporating linguistic uncertainties as type-2 fuzzy ANP method is firstly developed. ANP method has been selected as a MCDM in the decision process because of its capability to model dependencies and relations among all elements in decision making process. The fuzzy set theory (FST) can be also successfully applied for modeling the uncertainities which are derived from the human being's subjective evaluations. For this aim, type-2 fuzzy sets are applied. Consequently, the cities that should be given priority primarily in branding are determined.
Keywords: Decision making; fuzzy logic; analytic network process (ANP); type-2 fuzzy sets; brand cities; PROCESS INCAPABILITY INDEX; NETWORK PROCESS APPROACH; ENERGY ALTERNATIVES; SELECTION; MODEL; SETS; IMAGE; TRANSPORTATION; ORIENTATION; PERCEPTION; Computer Science; Science & Technology - Other Topics